2015
DOI: 10.1073/pnas.1509645112
|View full text |Cite
|
Sign up to set email alerts
|

On regreening and degradation in Sahelian watersheds

Abstract: Over many decades our understanding of the impacts of intermittent drought in water-limited environments like the West African Sahel has been influenced by a narrative of overgrazing and human-induced desertification. The desertification narrative has persisted in both scientific and popular conception, such that recent regional-scale recovery ("regreening") and local success stories (community-led conservation efforts) in the Sahel, following the severe droughts of the 1970s-1980s, are sometimes ignored. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 44 publications
9
70
1
1
Order By: Relevance
“…Regarding the aspect of topographic position, Kaptué et al (2015) confirmed an increasing woody cover at the watershed scale in the majority of their samples. The drier more northerly Sahelian watersheds in Senegal and eastern Mali appear to show stronger reforestation trends than the more mesic region of western Mali and the highly populated area near Niamey, Niger.…”
Section: Contributions Of Other Authorsmentioning
confidence: 78%
See 2 more Smart Citations
“…Regarding the aspect of topographic position, Kaptué et al (2015) confirmed an increasing woody cover at the watershed scale in the majority of their samples. The drier more northerly Sahelian watersheds in Senegal and eastern Mali appear to show stronger reforestation trends than the more mesic region of western Mali and the highly populated area near Niamey, Niger.…”
Section: Contributions Of Other Authorsmentioning
confidence: 78%
“…Based on these techniques, changes in vegetation pattern and density were quantified and mapped in the form of change detection maps showing "winners" (predominantly agriculture) and "losers" (vegetation) as a basis for planners and decision makers. The method was established in 1999 and has been further developed from 2001 on (Kusserow, 2001;Kirsch-Jung and Kusserow, 2002;Kusserow, 2010Kusserow, , 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rich and diverse scientific literature, covering various temporal and spatial scales, often disagrees with the overall trends of environmental change [4] but recent research suggests the Sahel is an unstable but resilient ecosystem which is steadily recovering from prolonged droughts and below average rainfall conditions [5]. The potential of recovery is especially favoured in areas of low human pressure and population density [5], and after droughts in activity over time (see Figures A1-A6 and Table 1). Soils play an important role in defining the contrasting character of the western and eastern parts of the study region.…”
Section: Introductionmentioning
confidence: 99%
“…These studies did not, however, allow separation of the contributions from the herbaceous and woody vegetation components. Only recently has this been achieved 18,19 revealing that the greening may be partly attributed to an increase in woody cover. The coarse spatial and limited temporal resolution of the satellite images used and the complexities of the methods applied imply that such assessments of vegetation change in the Sahel do not necessarily form a robust basis for estimating trends in woody cover locally, and leave considerable room for speculations regarding the nature of the woody vegetation changes.…”
Section: Introductionmentioning
confidence: 99%